As estratégias de convivência com o semiárido alicerçada no saber local: uma análise a partir do território Sertão do Araripe - PE - Teixeira, Cecilia Tayse Muniz (2020)
The present work aims to analyze, through the memories and strategies lived by the farming families in the face of the years of great droughts, showing how these farming families build, based on the accumulated life experiences, the local knowledge, towards the Coexistence with the Semi-Arid region Territory of ―Sertão do Araripe – PE‖. It is intended to know and understand the process of construction of the knowledge of the farming families, capable of enabling the Coexistence with the Semi-Arid, identifying, the forms of learning that these families use in the production of the local knowledge for permanence, in years of droughts , as well as to analyze how local knowledge is expressed in the social reproduction of rural farming families from their way of life, constituting a culture of living with the Semi-Arid that was built and learned for generations. The research methodology aimed to achieve subjective traits through a more holistic view of the facts and phenomena, for this we used as methodological instruments: a) analysis of the discourse of farming families; b) interpretation of the apprehended senses; c) participant observation. The analysis and construction of meanings for the thesis document was guided by the Theory of social representations. Thus, we present the context of the Brazilian Semi-Arid, highlighting in particular ―Sertão‖, the historiography of droughts in ―Sertão‖ and its impact on social formation, the identity construction of ―Sertões‖, the paths to living with the Semi-Arid, we also present the history of formation of the Brazilian Semi-Arid Articulation (ASA), and we intertwine with the meanings, memories of strategies of Coexistence with the Semi-Arid built by farming families. What allows us to realize that, the farming families of ―Sertão do Araripe‖, in particular, have their own system for monitoring and interpreting the Semi-Arid climate, the sabers acquired through past generations and by observing nature it help them in decision making, constitutes the way of life and prevented it in some way when a drought worsens, added to the water infrastructure, new management techniques, stock strategy, also worked with the extension action of the local NGOs, this set of strategies was responsible for a change in the survival condition for a Coexistence. Araripe‘s families demonstrate through the use of various methods of observing nature as part of the construction of knowledge for strategies of living with the semiarid region. The disclosure of this knowledge allowed us to understand that the production of knowledge is diversified, constitutes and reinforces the identity of social groups, is responsible for reconstructing thinking and influences social practices and the way of life of families. We identified that the construction of knowledge for living with the semiarid region is not definitive. It is a process in the making and is facing a great challenge. We found that strategies for living with the semiarid based on traditional knowledge, based on empirical experience, can be an important complement for the implementation of public policies in the semiarid, in addition to contributing to the meteorological forecasts that today only work on a probabilistic basis, by the institutes meteorological research.